Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)
\(\sqrt{\left(3-2\sqrt{2}\right)^2}-\sqrt{\left(\sqrt{8}-4\right)^2}=3-2\sqrt{2}-4+\sqrt{8}\)
\(=3-2\sqrt{2}-4+2\sqrt{2}=3-4=-1\)
b)
\(\frac{2}{\sqrt{3}-1}-\frac{2}{\sqrt{3}+1}=\frac{2\left(\sqrt{3}+1\right)-2\left(\sqrt{3}-1\right)}{3-1}\)
\(=\frac{2\left(\sqrt{3}+1-\sqrt{3}+1\right)}{2}=\sqrt{3}+1-\sqrt{3}+1=1+1=2\)
\(B=\frac{9\sqrt{5}+3\sqrt{27}}{\sqrt{5}+\sqrt{3}}=\frac{9\sqrt{5}+9\sqrt{3}}{\sqrt{5}+\sqrt{3}}=\frac{9\left(\sqrt{5}+\sqrt{3}\right)}{\sqrt{5}+\sqrt{3}}=9\)
\(C=\frac{\sqrt{2}+\sqrt{3}+\sqrt{6}+\sqrt{8}+4}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)
\(=\frac{\sqrt{2}+\sqrt{3}+\sqrt{6}+\sqrt{8}+\sqrt{4}+\sqrt{4}}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)
\(=\frac{\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)+\sqrt{2}.\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)
\(=\frac{\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)\left(\sqrt{2}+1\right)}{\sqrt{2}+\sqrt{3}+\sqrt{4}}=\sqrt{2}+1\)
mik chỉnh lại đề
\(D=\frac{3\sqrt{8}-2\sqrt{12}+\sqrt{20}}{3\sqrt{18}-2\sqrt{27}+\sqrt{45}}=\frac{6\sqrt{2}-4\sqrt{3}+2\sqrt{5}}{9\sqrt{2}-6\sqrt{3}+3\sqrt{5}}\)
\(=\frac{2\left(3\sqrt{2}-2\sqrt{3}+\sqrt{5}\right)}{3\left(3\sqrt{2}-2\sqrt{3}+\sqrt{5}\right)}=\frac{2}{3}\)
\(A=\frac{1}{\sqrt{11-2\sqrt{30}}}-\frac{3}{\sqrt{7-2\sqrt{10}}}+\frac{4}{\sqrt{8+4\sqrt{3}}}\)
\(=\frac{1}{\sqrt{6-2.\sqrt{6}.\sqrt{5}+5}}-\frac{3}{\sqrt{5-2.\sqrt{5}.\sqrt{2}+2}}+\frac{2}{\sqrt{4+2\sqrt{3}}}\)
\(=\frac{1}{\sqrt{\left(\sqrt{6}-\sqrt{5}\right)^2}}-\frac{3}{\sqrt{\left(\sqrt{5}-\sqrt{2}\right)^2}}+\frac{2}{\sqrt{\left(\sqrt{3}+1\right)^2}}\)
\(=\frac{1}{\sqrt{6}-\sqrt{5}}-\frac{3}{\sqrt{5}-\sqrt{2}}+\frac{2}{\sqrt{3}+1}\)
\(=\frac{6-5}{\sqrt{6}-\sqrt{5}}-\frac{5-2}{\sqrt{5}-\sqrt{2}}+\frac{3-1}{\sqrt{3}+1}\)
\(=\frac{\left(\sqrt{6}-\sqrt{5}\right)\left(\sqrt{6}+\sqrt{5}\right)}{\sqrt{6}-\sqrt{5}}-\frac{\left(\sqrt{5}-\sqrt{2}\right)\left(\sqrt{5}+\sqrt{2}\right)}{\sqrt{5}-\sqrt{2}}+\frac{\left(\sqrt{3}+1\right)\left(\sqrt{3}-1\right)}{\sqrt{3}+1}\)
\(=\sqrt{6}+\sqrt{5}-\sqrt{5}+\sqrt{2}+\sqrt{3}+1=\sqrt{6}+\sqrt{2}+\sqrt{3}+1\)
\(=\sqrt{2}\left(\sqrt{3}+1\right)+\sqrt{3}+1=\left(\sqrt{3}+1\right)\left(\sqrt{2}+1\right)\)
a/ \(\sqrt{8\left(\sqrt{2}-\sqrt{3}\right)^2}=2\sqrt{2}\left(\sqrt{3}-\sqrt{2}\right)=2\sqrt{6}-4\)
b/ \(ab\sqrt{1+\frac{1}{a^2b^2}}=ab.\sqrt{\frac{a^2b^2+1}{a^2b^2}}=\sqrt{a^2b^2.\frac{a^2b^2+1}{a^2b^2}}=\sqrt{a^2b^2+1}\)
c/ \(\sqrt{\frac{a}{b^3}+\frac{a}{b^4}}=\sqrt{\frac{a}{b^3}\left(1+\frac{1}{b}\right)}=\frac{1}{b}.\sqrt{\frac{a}{b}\left(1+\frac{1}{b}\right)}\)
d/ \(\frac{a+\sqrt{ab}}{\sqrt{a}+\sqrt{b}}=\frac{\sqrt{a}\left(\sqrt{a}+\sqrt{b}\right)}{\sqrt{a}+\sqrt{b}}=\sqrt{a}\)
a) Ta có: \(\sqrt{3+2\sqrt{2}-\sqrt{3-2\sqrt{2}}}\)
\(=\sqrt{3+2\sqrt{2}-\sqrt{2-2\cdot\sqrt{2}\cdot1+1}}\)
\(=\sqrt{3+2\sqrt{2}-\sqrt{\left(\sqrt{2}-1\right)^2}}\)
\(=\sqrt{3+2\sqrt{2}-\left|\sqrt{2}-1\right|}\)
\(=\sqrt{3+2\sqrt{2}-\left(\sqrt{2}-1\right)}\)
\(=\sqrt{3+2\sqrt{2}-\sqrt{2}+1}\)
\(=\sqrt{4+\sqrt{2}}\)
b) Ta có: \(\sqrt{7-4\sqrt{3}+\sqrt{12+6\sqrt{3}}}\)
\(=\sqrt{7-4\sqrt{3}+\sqrt{9+2\cdot3\cdot\sqrt{3}\cdot3}}\)
\(=\sqrt{7-4\sqrt{3}+\sqrt{\left(3+\sqrt{3}\right)^2}}\)
\(=\sqrt{7-4\sqrt{3}+\left|3+\sqrt{3}\right|}\)
\(=\sqrt{7-4\sqrt{3}+3+\sqrt{3}}\)
\(=\sqrt{10-3\sqrt{3}}\)
c) Ta có: \(\sqrt{5-2\sqrt{6}}+\sqrt{7+2\sqrt{10}}\)
\(=\sqrt{3-2\cdot\sqrt{3}\cdot\sqrt{2}+2}+\sqrt{2+2\cdot\sqrt{2}\cdot\sqrt{5}+5}\)
\(=\sqrt{\left(\sqrt{3}-\sqrt{2}\right)^2}+\sqrt{\left(\sqrt{2}+\sqrt{5}\right)^2}\)
\(=\left|\sqrt{3}-\sqrt{2}\right|+\left|\sqrt{2}+\sqrt{5}\right|\)
\(=\sqrt{3}-\sqrt{2}+\sqrt{2}+\sqrt{5}\)
\(=\sqrt{3}+\sqrt{5}\)
d) Ta có: \(\frac{\sqrt{8-2\sqrt{12}}}{\sqrt{3}-1}-\sqrt{8}\)
\(=\frac{\sqrt{6-2\cdot\sqrt{6}\cdot\sqrt{2}+2}}{\sqrt{3}-1}-\sqrt{8}\)
\(=\frac{\sqrt{\left(\sqrt{6}-\sqrt{2}\right)^2}}{\sqrt{3}-1}-\sqrt{8}\)
\(=\frac{\left|\sqrt{6}-\sqrt{2}\right|}{\sqrt{3}-1}-2\sqrt{2}\)
\(=\frac{\sqrt{6}-\sqrt{2}}{\sqrt{3}-1}-2\sqrt{2}\)
\(=\frac{2\left(\sqrt{3}-1\right)}{\sqrt{3}-1}-2\sqrt{2}\)
\(=2-2\sqrt{2}\)
Lời giải:
Ta có:
\(A=\frac{\sqrt{8-2\sqrt{12}}}{\sqrt{3}-1}-\sqrt{8}=\frac{\sqrt{6+2-2\sqrt{6.2}}}{\sqrt{3}-1}-2\sqrt{2}\)
\(=\frac{\sqrt{(\sqrt{6}-\sqrt{2})^2}}{\sqrt{3}-1}-2\sqrt{2}=\frac{\sqrt{6}-\sqrt{2}}{\sqrt{3}-1}-2\sqrt{2}\)
\(=\frac{\sqrt{2}(\sqrt{3}-1)}{\sqrt{3}-1}-2\sqrt{2}=\sqrt{2}-2\sqrt{2}=-\sqrt{2}\)